Reinterpretation of the Material and Meaning of the Encim Kebaya in the Dynamics of Social Practice - Winda Amalia; Fatmawati Fatmawati; Tri Wahyu Retno Ningsih (Longda Xiaokan: Journal of Mandarin Learning and Teaching, 2026)
This study aims to understand the dynamics of social practices surrounding the Kebaya Encim by focusing on changes in its material elements and meanings. The Kebaya Encim is a form of traditional attire that emerged from a blend of Javanese, Dutch, Chinese, and Betawi cultures, giving it strong historical and cultural significance within society. As times have changed, the Kebaya Encim is no longer used solely as traditional attire but has undergone transformations in both function and appearance to align with the needs and trends of modern society. This study employs the social dynamics theory proposed by Shove, Pantzar, and Watson (2012) to examine how changes in social practices occur through the interplay between material, competence, and meaning. The focus of this study is to examine the changes in the Kebaya Encim regarding its material elements and meanings resulting from social and cultural developments. The research method employed is descriptive qualitative, utilizing in-depth interviews, snowball sampling, as well as direct and digital observations via the social media platform TikTok. The results of the study indicate that the material elements of the Kebaya Encim have undergone changes in fabric, cut, motifs, color, and increasingly modern production technology. Meanwhile, the symbolic meaning of the Kebaya Encim has also evolved, encompassing its symbolic function, cultural identity, and the way people view it as part of their lifestyle and self-expression. These changes in both material and symbolic aspects influence one another and shape new social practices surrounding the use of the Kebaya Encim in contemporary society.